DAMPAK PENGEMBANGAN EKOWISATA MANGROVE TERHADAP MASYARAKAT LOKAL BATU LUMBANG DI DESA PEMOGAN, KOTA DENPASAR (Jurnal Destinasi Pariwisata, 2026)
The development of Batu Lumbang Mangrove Ecotourism in Pemogan Village, South Denpasar, is a community-based effort aimed at preserving the environment while improving the welfare of the local community. This area, which was previously quiet and unproductive, has now become an eco-friendly tourist destination with main activities such as mangrove tours, environmental education, and conservation. This phenomenon is worth studying because, in addition to its economic impacts, it also generates social dynamics within the community that can be analyzed using Doxey's Theory (1975). This research uses a qualitative descriptive approach with data collection techniques through in-depth interviews, field observations, and documentation studies. Informants consist of managers, local communities, and other related parties. The data obtained is analyzed by linking field findings to the concepts of ecotourism development, community participation, and Doxey's theory up to the annoyance stage. The results of the study show that the development of ecotourism has been taking place gradually since 2005, involving the fishing community as the main actors. Based on Doxey's theory, the Batu Lumbang community has gone through stages ranging from euphoria to apathy to early signs of annoyance, particularly in relation to the issue of waste carried by the river and limited human resources. Nevertheless, the relationship between the community and tourists remains positive thanks to the efforts of the managers in providing opportunities for participation through discussion forums and training. From an economic perspective, this ecotourism initiative has increased income, created jobs, and promoted equitable distribution of benefits, while maintaining environmental sustainability through the concept of limited tourism.
Keywords: Ecotourism; Mangroves; Socio-Economic; Community Participation; Sustainable Tourism